The future of vaccines for tuberculosis - Stockdale, L; Fletcher, H (Elsevier, 2019)
Exciting clinical results from 2 clinical TB vaccine trials were published in 2018. These, plus promising preclinical candidates form a healthy pipeline of potential vaccines against the leading cause of death from a single infectious agent. The only licensed vaccine, the BCG, continues to be an important tool in protecting against severe forms of TB in children, but has not stopped the diseases causing 1.3 million deaths per year. This review provides an overview of the current TB vaccine pipeline, highlighting recent findings, describes work relating to epidemiologic impact of vaccines, and discusses the future of TB vaccine development.